Enhancing the potential of solid waste minimization through waste bank programme: experience from higher education institutions in Malaysia - Alias, Fatma Sabariah; Abd Manaf, Latifah; Ho Nyuk Onn @ Ariffin, Mariani; Abdullah, Sabrina J. Ho (Malaysia Institute of Planners, 2019)
A voluntary approach for recycling programme can be enhanced by the establishment of waste bank in institutions of higher education. Hence, a waste bank programme was implemented in a “close loop” system at the Faculty of Environmental Studies, Universiti Putra Malaysia (FPAS, UPM). This aims to promote collection of recyclable materials and raise awareness among UPM students on the importance of recycling. Throughout the five (5) phases of operation, about 500 students were registered as waste bank members with the amount of total collected recyclables reaching 14,817.46 kg. The direct measurement method was applied in the waste bank operation procedure to weigh the recyclable materials received twice a week. The most frequent type of recyclable material collected was paper, including black/white paper, newspaper, and mix paper. The waste bank programme has enhanced the potential of solid waste minimisation by shifting the amount of waste disposed at the landfill site. Moreover, it enables recyclable materials to be seen as valuable resources as monetary rewards were given to encourage recycling practices among students based on the total weight for each collection of recyclable materials. Therefore, the implementation of the waste bank programme in Higher Education Institutions (HEI) in Malaysia creates an opportunity to be a medium of a sustainable solid waste minimisation system in promoting sustainable green campuses at the university.